2017
DOI: 10.1002/jctb.5232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH control on the anaerobic H‐B‐E fermentation of syngas in bioreactors

Abstract: BACKGROUND Syngas and some waste gases are composed mainly of carbon monoxide, carbon dioxide and hydrogen, which can be used by some acetogenic bacteria to produce ethanol, butanol or hexanol, and represents an attractive alternative to the conventional ABE (acetone–butanol–ethanol) fermentation. Experiments were carried out in bioreactors under different conditions (pH 5.75 and 4.75) with continuous supply of a mixture of CO/CO2/H2/N2 converted by Clostridium carboxidivorans into hexanol, butanol and ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…1, as this does also not affect the main goal and conclusions of the study, focusing on estimating salt inhibition. In any case, it can be stated that the production of such compound was similar as in other related studies (Fernández-Naveira et al 2017b, 2019). During the low pH conditions, CO consumption started decreasing down to 74–76% (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…1, as this does also not affect the main goal and conclusions of the study, focusing on estimating salt inhibition. In any case, it can be stated that the production of such compound was similar as in other related studies (Fernández-Naveira et al 2017b, 2019). During the low pH conditions, CO consumption started decreasing down to 74–76% (Fig.…”
Section: Resultssupporting
confidence: 87%
“…The medium used in the continuous gas-fed bioreactor experiment described here, and in similar experiments with C. carboxidivorans and syngas as a carbon source described in recent literature and the initial sodium chloride concentration (Fernández-Naveira et al 2016a, 2017b) correspond to the composition commonly recommended in the standard culture medium (2 g/L sodium chloride). This corresponds to an initial conductivity around 14 mS/cm.…”
Section: Resultsmentioning
confidence: 99%
“…A further important point of focus of this study was the evaluation of changes on the gas consumption profile of the culture. Not many studies can be found on the topic of syngas which show a system with the ability to track changes in the consumption of the gas substrates with on-line analytics, even if it is considered to be very relevant information [17]. In many cases, studies focusing on the effect of medium components or gas composition are performed in batch, with serum bottles, with the limitations that this implies (difficult pH control, no continuous gas feed and no possibility of out-gas analysis).…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of fermentation (4 to 5 h), a decrease in pH values before glucose depletion is detected, and this is followed by an increase in pH levels on both media. These phases are described in literature as acidogenesis and solventogenesis [27].…”
Section: Metabolites Productionmentioning
confidence: 99%